Comparison of visual simple reaction time performances of boxers and wrestlers - Dinçer, N.; Kilinç, Z.; Ilbak, I. (Pakistan Journal of Medical and Health Sciences, 2022)
Background: It is known that reaction time, which is of great importance in terms of athlete performance, is one of the most difficult sports performance parameters to develop. Reaction time performance in Athletes may vary according to the sport branch in terms of development. Especially in combat sports such as boxing and wrestling, reaction time is of such great importance that it can directly or indirectly affect the outcome of the competition.